A polar TiO/MWCNT coating on a separator significantly suppress the shuttle effect in a lithium-sulfur battery. (1st July 2019) - Li, Zhi; Tang, Linbin; Liu, Xiaohao; Song, Tianbing; Xu, Qunjie; Liu, Haimei; Wang, Yonggang
Abstract：: Lithium-sulfur (Li-S) batteries are extremely attractive because of their high theoretical capacities, energy densities, and cost-effectiveness, as well as the environmental friendliness of elemental sulfur. However, the commercialization of Li-S batteries is impeded by fast capacity fading and harsh self-discharge. To overcome these issues, effort has been dedicated to improving performance by designing the electrode structure and composition, which is often expensive and complex. In this study, modification of the separator by a combination of commercial titanium monoxide and multiwall carbon nanotubes (TiO/MWCNTs) was first designed, which is a low-cost and simple preparation process. The cooperative effect of TiO and MWCNTs capacitates the feedback of the Li-S cell with a relatively high premier discharge capacity of 1527.2 mAh g −1, and excellent cycling stability is obtained up to 1000 cycles at 0.5 C with a negligible fading rate of 0.057% per cycle. And the self-discharge behavior was improved obviously. When the time of rest was extended to 96 h, the capacity attenuation of the cell with the TiO/MWCNT coating was only 12.4%. The use of a TiO/MWCNT-coated separator is a feasible method for the commercial success of high-performance Li-S batteries. Graphical abstract: Image 1 Highlights: TiO/MWCNT composite is firstly used to modify the separator of Li-S battery. High density of oxygen and titanium vacancies of TiO is benefit for adsorbing LiPSs. MWCNT network as a physical barrier improves the conductivity of the separator. The strong adsorption of TiO/MWCNT suppress the shuttle effect of Li-S battery.